Impact of carbon dioxide and increasing nitrogen levels on growth, photosynthetic capacity, carbohydrates and secondary metabolites in Kacip Fatimah (Labisia pumila) - Ibrahim, Mohd Hafiz; Jaafar, Hawa Z. E. (Sciencedomain International, 2017)
Aims: This study was designed to investigate how CO2 and nitrogen availability alters growth, leaf gas exchange, primary and secondary metabolites production (total phenolics and flavonoid) in three varieties of L. pumila. namely var alata, var pumila and var lanceolata. under CO2 enrichment (1200 µmol mol-1) combined with four levels of nitrogen fertilization (0, 90, 180 and 270 kg N ha-1) for 15 weeks. Study Design: Three-month old L. pumila seedlings of var. alata, var. pumila and var. lanceolata were left for a month to acclimatize in a nursery until ready for the treatments. Carbon dioxide enrichment treatment started when the seedlings reached 4 months old where plants were exposed to 1200 µmol-1 mol-1 CO2 and fertilized with four levels of nitrogen concentrations viz. 0, 90, 180 and 270 kg N Ha-1. The fertilization with nitrogen levels were split into three applications. A control at ambient CO2 (400 µmol-1 mol-1) with standard N fertilization (180 kg N ha-1) was included to compare plant responses to high CO2 combined with different levels of N. Place and Duration of Study: Faculty of Agriculture Glasshouse Complex, Universiti Putra Malaysia from February to May 2011. Methodology: The seedlings were raised in specially constructed growth houses receiving 12-h photoperiod and average photosynthetic photon flux density of 300 µmol m-2 s-1. Carbon dioxide at 99.8% purity was supplied from a high–pressure CO2 cylinder and injected through a pressure regulator into fully sealed 2 m x 3 m growth houses at 2-h daily and applied continuous from 800 to 1000. Total plant biomass was taken by calculating the dry weight of root, stem and leaf per seedling. Total leaf area per plant was measured using a leaf area meter (LI-3100, Lincoln Inc, USA). The measurement of photosynthesis was obtained from a closed system of infra-red gas analyzer LICOR 6400 Portable Photosynthesis System. The response of net CO2 exchange (A) to changing intercellular CO2 concentration (Ci) was conducted at 27°C, 50% relative humidity and at light saturating conditions of 800 µmol m-2s-1. Anthrone method was used to determine the content of total available carbohydrate. Follin–Ciocalteau reagent was used to determine total phenolics and flavonoid using spectrophotometer. Results: In all parameters measured there were no significant was observed in the three varieties. As the levels of nitrogen increased from 0 to 270 kg N ha-1, plant growth, photosynthesis and total chlorophyll content was enhanced. However, carbohydrate, total phenolics and flavonoid was reduced with the increase in nitrogen fertilization. It was found that the high application of nitrogen can increased the photosynthetic capacity of L. pumila by having high Vcmax (RuBisCO CO2 fixation capacity), A sat (CO2 saturation point) and low dark respiration rate in the analysis of A/Ci curves. The production of secondary metabolites was related to increased total non-structural carbohydrate (TNC) under low nitrogen condition. Photosynthesis, displayed a significant negative relationship with secondary metabolites production. Total chlorophyll content exhibited very significant negative relationships with total soluble sugar, starch and total non-structural carbohydrate. Conclusion: This study demonstrated that enrichment with high levels of CO2 is able to enhance the production of plant secondary metabolites. However, increased nitrogen fertilization can reduce the production of these plant secondary metabolites under CO2 enrichment. When there were accumulation of TNC in plant leaves and reduction in photosynthesis, the production of plant secondary metabolites might be up-regulated. The increase in the production of plant secondary metabolites was indicated by reduction in chlorophyll contents.